Pricing of Complements in the U.S. Freight Railroads: Cournot Versus Coase - Alexei Alexandrov; Russell Pittman; Olga Ukhaneva (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2017)
Monopolists selling complementary products charge a higher price in a static equilibrium than a single multiproduct monopolist would, reducing both the industry profits and consumer surplus. However, firms could instead reach a Pareto improvement by lowering prices to the single monopolist level. We analyze administrative nationally-representative pricing data of railroad coal shipping in the U.S. We compare a coal producer that needs to ship from A to C, with the route passing through B, in two cases: (1) the same railroad owning AB and BC and (2) different railroads owning AB and BC. We do not find that price in case (2) is higher than price in case (1), suggesting that the complementary monopolist pricing ineficiency is absent in this market. For our main analysis, we use a specification consistent with the previous literature; however, our findings are robust to propensity score blocking and machine learning algorithms. Finally, we perform a difference-in-differences analysis to gauge the impact of a merger that made two routes wholly-owned (switched from case 2 to case 1), and these results are also consistent with our main findings. Our results have implications for vertical mergers, tragedy of the anticommons, mergers of firms selling complements, and royalty stacking and patent thickets.
Keywords: 330